Analisis tingkat kontaminasi permukaan daerah kerja dan laju paparan radiasi pada Instalasi Kedokteran Nuklir - Ukhti Lailun Nisa; Gani Gunawan; Zaenal Arifin; Eko Hidayanto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
The surface contamination of the work area and the rate of radiation exposure at nuclear medicine installation have an effect to the safety workers and the society directly or indirectly. This study aims to analyze the level of surface contamination and the rate of radiation exposure on the nuclear medicine installation and to identify the activity of half time 99mTc and 131I. The used method is measuring the surface contamination of the work area caused by the use of radiopharmaceutical through the distance between the detector window and the 3 cm measured region. Meanwhile, the rate of radiation exposures is used to measure the sides of each room with a distance 1 meter in the area control and to measure the activity of radioisotope that is monitored once every an hour for 6.03 hours to 99mTc and every day for 8 days to 131I of the initial measurement and compares with the result calculation. The measurement result of the level of the surface contamination in various areas of all rooms is 0.000-5.272 Bq/cm2 and it is classified into low to medium level of contamination. The measurement result of the rate of radiation exposure in the control area is 0.022-1.404 µSv/h which is still classified under 10 µSv/h. So, it can be concluded that it is safe for workers and other patients. The use of radioisotope on the nuclear medicine installation in accordance with their needs and always consider to the principles of the radiation protection, therefore the level of contamination and the rate of radiation exposure is low. The result of the measurement and the calculation of the activity of 99mTc are decays into a half after 6.03 hours and the activity of 131I is decays a half after 8 days. Keywords: Radiation Protection, Contamination, The rate of Radiation Exposure Half Time Activity.